Manifesto - Grupo de Estudos sobre Assessoria Pedagógica Universitária - Xavier, Amanda Rezende Costa; Azevedo, Maria Antonia Ramos de; Sousa, Waleska Dayse Dias de; Wagner, Flavia (Educação: Teoria e Prática, 2023)
Não se aplica.